Sex and social media - Tiidenberg, Katrin; Nagel, Emily van der (SocietyNow., 2020)
Sex and Social Mediaoffers a curious reader an academically informed yet accessible discussion of the nuances of sexual social media and socially mediated sex, giving a much-deserved space to explore the multiplicity and richness of sexual practices online.